Pediatric non-alcoholic fatty liver disease: current perspectives on diagnosis and management - Di Sessa A; Cirillo G; Guarino S; Marzuillo P; Miraglia del Giudice E (Dove Medical Press, 2019)
Anna Di Sessa, Grazia Cirillo, Stefano Guarino, Pierluigi Marzuillo, Emanuele Miraglia del GiudiceDepartment of Woman, Child and General and Specialized Surgery, University of Studies of Campania “Luigi Vanvitelli”, Napoli 80138, ItalyCorrespondence: Pierluigi MarzuilloDepartment of Woman, Child and General and Specialized Surgery, University of Studies of Campania “Luigi Vanvitelli”, 80138 Napoli, ItalyTel +39 081 566 5465Email pierluigi.marzuillo@gmail.comAbstract: Non-alcoholic fatty liver disease (NAFLD) represents the most common cause of chronic liver disease in childhood. To date, the “multiple-hit” hypothesis is largely recognized as an explanation of NAFLD pathogenesis and progression. Obesity and features of the metabolic syndrome have been closely linked to NAFLD development. Due to the increased prevalence of obesity worldwide, NAFLD has reached epidemic proportions over time. Given its unfavorable cardiometabolic burden (such as cardiovascular and metabolic consequences), it represents a worrying phenomenon needing a more comprehensive and successful management. Laboratory tests and classical imaging techniques play a pivotal role in NAFLD diagnosis, but novel noninvasive alternative methods to diagnose and monitor NAFLD have been investigated. Currently, lifestyle modifications remain the mainstay treatment, although its efficacy is poor because of the lack of compliance. Pediatric research is focusing on multiple alternative treatments targeting the main pathogenic factors such as insulin-resistance, dyslipidemia, gut-liver axis and microbiota, oxidative stress, and proinflammatory pathways. Results from these studies are promising but larger validation is needed. Innovative therapeutic approaches might add an important piece in the complex knowledge of pediatric NAFLD. We aimed to summarize recent insights into NAFLD diagnosis and treatment in children, with a focus on possible future perspectives in pediatric research.Keywords: fatty, liver, pediatric, diagnosis, management